Protein‐Inspired Polymers with Tunable Microphase Structures toward Autonomous Self‐Healing in Aqueous Environments - Yanwen Hu; Yan Song; Guo Liang Li (Advanced Materials Interfaces)
Abstract The self‐healing of polymer materials in aqueous environments remains a significant challenge. Herein, a protein‐inspired strategy for hydrophobic/hydrophilic‐induced microphase separation is proposed to construct self‐healing polymers in an aqueous environment. During self‐healing, the hydrophobic polydimethylsiloxane microphases in the damaged region reassociate with each other owing to the presence of dynamic hydrophobic interactions underwater. In addition, the hydrophilic carboxyl groups diffuse and penetrate to form hydrogen bonds. It is found that the microphase structure and self‐healing efficiency can be adjusted by regulating the hydrophobic/hydrophilic components. The self‐healing efficiencies of the as‐synthesized polymers in deionized water and seawater environments reach to 99.1 and 98.7%, respectively. The molecular structures of the materials are characterized using Fourier‐transform infrared spectroscopy and ultraviolet‐visible spectroscopy while the aggregated structure of the as‐synthesized polymers is examined using small angle X‐ray scattering and atomic force microscopy (AFM). This design strategy, inspired by the biological sciences, will be expected to extend the application range of synthetic intrinsic self‐healing polymers, especially in aqueous environments.